Role of Cannabis in the Management of Chronic Non-Cancer Pain: A Narrative Review - Lou’i Al-Husinat; Shrouq Obeidat; Saif Azzam; Yara Al-Gwairy; Fatima Obeidat; Sarah Al Sharie; Deema Haddad; Fadi Haddad; Martina Rekatsina; Matteo Luigi Giuseppe Leoni; Giustino Varrassi (Clinics and Practice)
Chronic non-cancer pain, defined by the Center for Disease Control and Prevention (CDC) as lasting beyond three months, significantly affects individuals’ quality of life and is often linked to various medical conditions or injuries. Its management is complex. Cannabis, containing the key compounds Delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD), has garnered interest for its potential in pain management, though it remains controversial due to its psychoactive effects and illegal status in many countries. THC provides pain relief by blocking nociceptive stimuli but has psychoactive effects and may potentially induce dependency. CBD has calming and antipsychotic properties. The inhalation of cannabis offers quick relief but poses respiratory risks, while its oral administrations are safer but act more slowly. Short-term cannabis use can impair cognition and motor skills, while long-term use may lead to dependency and cognitive decline, especially if used from an early age. Adverse effects vary by gender and prior use, with addiction mainly linked to THC and influenced by genetics. Despite these risks, patients often report more benefits, such as improved quality of life and reduced opioid use, although the evidence remains inconclusive. The legal landscape for medical cannabis varies globally, with some positive public health outcomes like reduced opioid-related issues in areas where it is legalized. Cannabis shows promise in managing chronic pain, but its psychoactive effects and dependency risks necessitate cautious use. Future research should prioritize long-term clinical trials to establish optimal dosing, efficacy, and safety, aiding in the development of informed guidelines for safe cannabis use in chronic pain management. This review examines the use of cannabis in managing chronic non-cancer pain, focusing on its benefits, drawbacks, mechanisms, delivery methods, and impact on quality of life.